Janácek's Operas : A Documentary Account - Janáček, Leoš, 1854-1928 (Book collections on Project MUSE., 1992)
One of the most original and engaging composers of the twentieth century, Leos Janáçek is now regarded as one of its major musical dramatists. His operas have become a regular part of the repertory, but a full understanding of their diverse subjects and backgrounds has been hampered by the lack of source materials in English. John Tyrrell has here selected and translated the chief literary documents relating to the genesis and early performances of each of the composer's nine operas and presented them in the form of a compelling documentary narrative. Janáçek was a vigorous letter-writer and kept every letter he received. A vast quantity of material on his life has survived, providing a unique insight into his working methods and attitudes toward his operas. Scrupulously translated and annotated, the sources in this volume have not previously been brought together in this way. Some have appeared in scattered and often inaccessible publications in Czech, and others, such as the sequence of daily letters that Janáçek wrote to his wife during the rehearsals for the Prague premiere of Jenufa, or his instructions to his librettist for Fate, have never been published before. The book is complemented by a chronology of Janáçek's operas keyed to the numbered documents in each chapter, a bibliography, and a list of sources. Drawing on twenty-five years of work at the Janáçek archive in Brno, this work is a classic of music documentary scholarship.Originally published in 1992.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.